Influencing Human Interaction — Eleven Years with IPR - Kagan, Norman (Canadian Journal of Counselling and Psychotherapy, 2012)
IPR (Interpersonal Process Recall) is proving to be an effectivemethod using videotape procedures to help counsellors in trainingbecome more sensitively aware of their own reactions and their effect onothers. Most importantly, this process is an encouraging, growth-inducingone with potential for uses with other groups concerned with personalrelationships.